Characterization of key odorants in peeled and unpeeled flaxseed powders using solvent-assisted flavor evaporation and odor activity value calculation. (March 2021) - Yang, Yini; Deng, Qianchun; Jia, Xiao; Shi, Jie; Wan, Chuyun; Zhou, Qi; Wang, Qiang
Abstract: Flaxseed powder is a widely used nutrient-rich food, valued for its flavor as well as its nutritional value. The effect of peeling on the flavor profiles of raw and microwaved flaxseed powder remains unclear. In this study, the volatile components of flaxseed powder were analyzed using solvent-assisted flavor evaporation combined with gas chromatography-mass spectrometry-olfactometry. Fifty-two odor-active compounds were identified, with flavor dilution (FD) factors ranging from 3 to 729. Hexanal, d -limonene, 1-hexanol, β -phellandrene, α -phellandrene, and nonanal with Odor Activity Values (OAV≥1), which could impart green-like, fresh-like, and mint-like notes, were the typical odorants in raw flaxseed powders. Microwaved powders had more intense roasted and woody notes than raw powders. Peeling treatment had a significant effect on the aroma of microwaved flaxseed powder, but caused only a slight change in the flavor profiles of the raw powders. The key aroma differences in the two kinds of microwaved powders were mainly due to the levels of 2-methylbutanal, 2-methylpyrazine 6-methyl-5-hepten-2-ol, 4-hydroxy-2, 5-dimethylfuran-3-one, 2-ethyl-3, 6-dimethylpyrazine, and 2-ethyl-3, 5-dimethylpyrazine. This work provides a basis for the improvement of the aroma of flaxseed products. Highlights: Volatile components of flaxseed powder were analyzed. Fifty-two odor-active compounds were identified. Microwaved powders had more intense roasted and woody notes than raw powders. Peeling had a significant effect on the aroma of microwaved flaxseed powder.